Genômica comparativa de um baculovírus isolado da lagarta praga Rachiplusia nu (Guenée) (Lepidoptera: noctuidae) - Trentin, Luana Belo (2019)
We described a novel baculovirus isolated from the polyphagous insect pest Rachiplusia nu. The virus presented pyramidal-shaped occlusion bodies (OBs) with singly-embed nucleocapsids and a dose mortality response of 6.9 × 103OBs/ml to third-instar larvae of R. nu. The virus genome is 128,587 bp long with a G + C content of 37.9% and 134 predicted ORFs. The virus is an alphabaculovirus closely related to Trichoplusia ni single nu-cleopolyhedrovirus, Chrysodeixis chalcites nucleopolyhedrovirus, and Chrysodeixis includens single nucleopolyhedrovirus and may constitute a new species. Surprisingly, we found co-evolution among the related viruses and their hosts at species level. Besides, auxiliary genes with homologs in other baculoviruses were found, e.g. a CPD-photolyase. The gene seemed to be result of a single event of horizontal transfer from lepidopterans to alphabaculovirus, followed by a transference from alpha to betabaculovirus. The predicted protein appears to be an active enzyme that ensures likely DNA protection from sunlight.